THE EFFECTIVENESS OF THE APPLICATION OF SCIENTIFIC LITERACY-BASED NATURAL SCIENCE TEACHING SET TOWARD THE STUDENTS’ LEARNING ACTIVITIES AND OUTCOMES ON THE TOPIC OF THE INTERACTION OF LIVING ORGANISM AND ENVIRONMENT (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This research was aimed to find out effectiveness of the application of scientific literacy-based natural science teaching set toward the students’ learning activities and outcomes on the topic of The Interaction of Living Organism and Environment. This study is a quasi-experimental study of non-equivalent type (pretest-posttest). The results showed that the teaching set was effective, as proved by the t-test of the learning outcomes of the experimental group (t4,78 t1,66) which was different to the control group (thitungt1,66), the results of the experiment group n gain average was 0,55 and the control group was 0,39 which was in the average category. The t-test value of the activities in the experimental group (t3,52t1,66) was different to the control group (thitungt1,66). Based on the analysis results, it could be concluded that the application of the scientific literacy-based natural science teaching set was effective toward the students’ learning activities and outcomes.